2018
DOI: 10.14214/sf.9923
|View full text |Cite
|
Sign up to set email alerts
|

Value of airborne laser scanning and digital aerial photogrammetry data in forest decision making

Abstract: Highlights• Airborne laser scanning (ALS) and digital aerial photogrammetry (DAP) are nearly equally valuable for harvest scheduling decisions even though ALS data is more precise.• Large underestimates of stand volume are most dangerous errors for forest owner because of missed cutting probabilities.• Relative RMSE of stand volume and the mean volume in a test area explain 77% of the variation between the expected losses due to errors in the data in the published studies.• Increasing the relative RMSE of volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 23 publications
(40 reference statements)
2
31
0
2
Order By: Relevance
“…Three-dimensional (3D) RS data, which can describe tree or canopy height, have shown great potential for forest inventory [4]. In the past 20 years, the use of airborne laser scanning (ALS) has been widely used for forest inventory purposes and has become the standard data source for operational forest inventories in many countries around the world [5][6][7]. Nevertheless, the acquisition of ALS data requires a degree of planning and investment, making these data sources cost-effective only on a relatively large scale [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three-dimensional (3D) RS data, which can describe tree or canopy height, have shown great potential for forest inventory [4]. In the past 20 years, the use of airborne laser scanning (ALS) has been widely used for forest inventory purposes and has become the standard data source for operational forest inventories in many countries around the world [5][6][7]. Nevertheless, the acquisition of ALS data requires a degree of planning and investment, making these data sources cost-effective only on a relatively large scale [8].…”
Section: Introductionmentioning
confidence: 99%
“…This data synergy has been thoroughly discussed by Goodbody et al [11], indicating the potential for cost-efficient forest inventory updates. Similarly, Kangas et al [6] suggest an equal value of photogrammetric and ALS data in forest management planning, given that a ALS ground information is available from previous campaigns. Additional to the proven complementary use of LiDAR and photogrammetric data [9,11,12], recent attempts at deriving inventory relevant forest metrics from photogrammetric data alone show potential for aerial [13•, 14] and terrestrial [15•, 16] acquisitions.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a substantial research effort has been directed at assessing the capability of photogrammetric methods to generate canopy and tree-level metrics that support estimation of forest inventory (Nurminen et al 2013;White et al 2015;Bonnet et al 2017;Goodbody et al 2017;Ota et al 2017;Alonzo et al 2018;Caccamo et al 2018;Guerra-Hernández et al 2018;Navarro et al 2018;Iqbal et al 2019). These studies have demonstrated that DAP and photogrammetric methods are a practical alternative to airborne laser scanning (ALS) for the purposes of forest inventory when there are sufficient operational and financial benefits (Kangas et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The value of the information contained in forest inventory data can be examined using cost-plus-loss (CPL) analysis (Hamilton 1978;Burkhart et al 1978), in which the losses due to non-optimal decisions caused by inaccurate data are added to the total costs of the forest inventory (Eid 2000;Borders et al 2008;Duvemo 2009;Islam et al 2009;Mäkinen et al 2012;Kangas et al 2018a). Losses occur when sub-optimal decisions are made because of erroneous data, and their magnitudes usually increase with the uncertainty of the data.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the interest has been more in three-dimensional digital aerial photogrammetry data (3D), which have been seen as a promising and clearly cheaper data source than ALS data (e.g. Ørka et al 2013;Kangas et al 2018a). However, the use of three-dimensional aerial data necessitates an available digital terrain model.…”
Section: Introductionmentioning
confidence: 99%